1978
DOI: 10.1161/01.res.42.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of regional oxygen consumption in the dog heart.

Abstract: ENERGY COSTS vary with an organ's functional needs. The same relationship applies within different regions of the same organ. In vivo regional differences in O t consumption are known within some organs, e.g., white and gray matter of the cerebral cortex, subepicardium, and subendocardium of the left ventricle, and cortex and medulla of the kidney. "3 Only qualitative evidence for these differences exist. We have developed a technique that can quantitatively measure these differences in regional O 2 consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(64 citation statements)
references
References 27 publications
6
55
2
1
Order By: Relevance
“…The left ventricular myocardium demonstrates transmural heterogeneity of strain distribution. It has been reported that, under normal circumstances, the subendocardial myocardium receives more blood flow and consumes more oxygen than the subepicardial one (20,28,35). Moreover, there is a transmural gradient of contractile function in the left ventricular wall, with greatest amount of thickening occurring in the subendocardial myocardium (6,25).…”
Section: Discussionmentioning
confidence: 99%
“…The left ventricular myocardium demonstrates transmural heterogeneity of strain distribution. It has been reported that, under normal circumstances, the subendocardial myocardium receives more blood flow and consumes more oxygen than the subepicardial one (20,28,35). Moreover, there is a transmural gradient of contractile function in the left ventricular wall, with greatest amount of thickening occurring in the subendocardial myocardium (6,25).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and limitations of the method used to determine regional 02 consumption has been described in detail previously (22)(23)(24). Briefly, the accuracy of our determination of 02 consumption depends on the accuracy of the determination of arterial and venous 02 content and blood flow as well as the limitations of the Fick principle itself.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared for analysis of regional microsphere distribution and for microspectrophotometric analysis as described (24). Briefly, 30 um-thick frozen tissue sections were cut on a cold rotary microtome in a -25°C cold box in an N2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After polishing the cut surfaces of quick-frozen pieces of myocardium, Weiss et al (102) measured spectrophotometrically the hemoglobin saturation with oxygen in small arteries and veins, and demonstrated that more oxygen was used in high-flow regions than in low-flow regions. Caldwell et al (27) observed that the local capacity for the uptake of fatty acid was proportional to the regional flows in the hearts of dogs running on the treadmill.…”
Section: Substrate Uptake Ratesmentioning
confidence: 99%